PENINGKATAN KETERAMPILAN MEMBACA SISWA KELAS V SDN TLESA MELALUI DONGENG RAKYAT MADURA - kusyairi, kusyairi; Khoiri, M.; Khotijah, Siti (IDEALITA: Jurnal Pendidikan dan Sosial Keagamaan, 2022)
The purpose of the study was to determine the improvement of reading skills of elementary school students through Madura folk tales in fifth grade students of SDN Tlesa. Based on the research used is classroom action research. Data collection was obtained by means of observation, interviews, and documentation conducted in April-May 2022. Data analysis used data presentation, and drawing conclusions. To check the findings using source triangulation. After the data is collected from the results of the questionnaire answers and observations, the data will be tabulated to quantify the answers of the informants and observations which will be described in the form of excel application assistance. The results showed that the skill in obtaining an average value of the first cycle (1.66) could increase against the second cycle, obtaining an average value of 3.51. So in the first cycle got the criteria (enough), but there was the second cycle got the criteria (very good). So there is an increase of 1.85 from cycle I to cycle II.